PENGARUH SENAM LANSIA TERHADAP KUALITAS TIDUR PENDERITA HIPERTENSI PADA LANSIA - Djunizar Djamaludin (Universitas Malahayati Lampung, 2019)
ABSTRACT : THE EFFECTS OF GYMNASTICS EXERCISE ON THE SLEEP QUALITY OF ELDERLY PATIENTS WITH HYPERTENSION Background: Elderly often experiences declines in terms of social, economy, and health. Data in 2013 showed that the most often elderly’s diseases were hypertension, arthritis, and stroke (Ministry of Health of Republic of Indonesia, 2013). According to National Sleep Foundation, 67% from 1508 elderly more than 60 years old in America suffered sleeping difficulties and 7.3% suffered insomnia (Breus, 2004). Elderly exercise will improve relaxation and help to improve elderly sleep. Data in Talang Jawa public health center in Merbau Mataram sub districtof South Lampung district in 2015 showed that there were averagely 248 elderly with 50 of them suffering hypertension.Purpose :The objective of this research was to find out the influence of elderly exercise to sleeping quality of elderly hypertension patients in Talang Jawa public health center in Merbau Mataram sub district of South Lampung district in 2016.Methods :This was a quantiattive research with quasi-experiment approach. Population was 57 elderly with hypertension in July 2015 Talang Jawa public health center. Samples were 42 respondents. Data were collected with Pittsburg Sleep Quality index (PSQI) questionnaire to estimate the sleeping quality. Data were analyzed with t-independent test.Results: The results showed that 13 respondents (61.9%) joined the elderly exercise and had good sleeps. 16 respondents (76.2%) did not join elderly exercise and had poor sleep. There was an influence of elderly exercise to sleeping quality of elderly hypertension patients in Talang Jawa public health center in Merbau Mataram sub district of South Lampung district in 2016 (p-value = 0.030)]Conclusion : the study showed effectiveness of gymnastics exercise on the quality of sleep of the elderly. It is recommended that elderly integrated health service post (posyandu lansia) and elderly nursing home to improve promotion efforts and to teach elderly exercise to overcome sleep quality decrease at elderly. Keywords : gymnastics exercise, elderly, sleep quality Pendahuluan :Lansia banyak mengalami kemunduran dari segi sosial, ekonomi, dan kesehatan. Pada tahun 2013, diperoleh data 3 penyakit terbanyak lansia yaitu (hipertensi, arthritis, dan stroke) (Kemenkes RI, 2013). Menurut National Sleep Foundation 67% dari 1.508 lansia di Amerika usia 60+ tahun mengalami gangguan tidur dan 7,3% gangguan insomnia (Breus,2004). Senam lansia akan meningkatkan relaksasi, dan membantu peningkata kebutuhan tidur lansia. Puskesmas Rawat Inap Talang Jawa Kecamatan Merbau Mataram Lampung Selatan Tahun 2015, didapatkan data dengan rata-rata selama 1 tahun, jumlah lansia 248 dan dengan hipertensi 50 responden.Tujuan : Tujuan dari penelitian ini adalah diketahui pengaruh senam lansia terhadap kualitas tidur penderita hipertensi pada lansia di Wilayah Puskesmas Rawat Inap Talang Jawa Kecamatan Merbau Mataram Lampung Selatan Tahun 2016.Metode :Jenis penelitian kuantitatif dengan pendekatan quasi eksperimen. Populasi pada penelitian ini adalah lansia menderita hipertensi di Wilayah Kerja Puskesmas Rawat Inap Talang Jawa, lansia dengan hipertensi terbanyak pada bulan Juli tahun 2015, sejumlah 57 responden, menggunakan metode purposive sampling yaitu 42 responden. Instrument pengumpulan data dalam penelitian ini menggunakan kuesioner PSQI (Pittsburgh Sleep Quality Index) untuk menghitung kualitas tidur. Uji statistik yang digunakan uji T-Independen.Hasil : Didapatkan responden yang mengikuti senam dengan kualitas tidur kategori baik, yaitu 13 responden (61,9%). Responden yang tidak mengikuti senam dengan kualitas tidur kategori buruk, yaitu 16 responden (76,2%). Penelitian juga didapatkan ada pengaruh senam lansia terhadap kualitas tidur penderita hipertensi pada lansia di Wilayah Puskesmas Rawat Inap Talang Jawa Kecamatan Merbau Mataram Lampung Selatan Tahun 2016 dengan (p value = 0,030).Simpulan : Saran bagi pelayanan di posyandu lansia dan panti jompo, yaitu dengan meningkatkan upaya promosi dan mengajarkan senam lansia untuk mengatasi penurunan kualitas tidur, pada lansia. Kata Kunci: Senam lansia, Kualitas Tidur, Hipertensi